Nickel, cobalt, and their alloys - Davis, Joseph R (ASM specialty handbook, 2000)
Introduction to nickel and nickel alloys - Corrosion behavior of nickel and nickel alloys - Fabrication and finishing of nickel and nickel alloys - Metallography, microstructures and phase diagrams of nickel and nickel alloys - Introduction to cobalt and cobalt alloys - Properties and fabrication characteristics of cobalt and cobalt alloys.